Revisiting Military Expenditure and Economic Growth Nexus in Nigeria: A Wavelet Approach - Lawal, Esther Omotola; Musa , Dasauki Caleb; Kwarbai, Jerry Danjuma; Okedina, Iyabo Mary; Oloyede , Binuyo Babatunde; Ebere , Chidinma Edith; Osundina, Olawumi Abeni (Journal of Ecohumanism, 2024)
This study examined the relationship between defence expenditure and economic growth in Nigeria. The ARDL model and wavelet coherence test were applied using time series data covering 1960 to 2018, obtained from the World Bank. Military expenditure has a negative short-run impact on economic growth. Arms import and the military regime increased economic growth rate in the short run but the growth rate declined in the long run. Wavelet Coherence result shows that military expenditure leads economic growth, in other words, the growth impact of military expenditure is temporal. Military expenditure is benefitial to the Nigerian Economy in the long run but has a negative short term effect. The military regime has a negative long-run impact on the economic growth rate. The role of the military in governance should be minimized. Military should concert effort in national defense and not governance.